Learning English phrasal verbs through interactive text-messaging - Abadikhah, Shirin; Rastegar, Sanaz (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study was carried out to investigate the effectiveness of interactive text-messaging in learning English phrasal verbs by Iranian EFL learners. The study employed a pre-test, post-test quasi-experimental design with two experimental groups exposed to two learning conditions (paper-based and SMS-based) and a control group. Forty-eight EFL learners were assigned into two experimental and one control group(s). The participants in each experimental group were divided into four smaller groups and performed an interactive task (i.e.,expand the story) in two different ways. The results indicated that although both groups improved significantly from pre-test to post-test and did significantly better than their counterparts in the control group, the SMS-based group outperformed the paper-based group in learning English phrasal verbs. Furthermore, the results of the delayed post-test showed that the participants in the SMS-based group had significantly more vocabulary gains than their paper-based counterparts.